2007
DOI: 10.1111/j.1525-1438.2007.00921.x
|View full text |Cite
|
Sign up to set email alerts
|

A case-controlled study of total laparoscopic radical hysterectomy with pelvic lymphadenectomy versus radical abdominal hysterectomy in a fellowship training program

Abstract: To determine whether total laparoscopic radical hysterectomy (TLRH) is a feasible alternative to an abdominal radical hysterectomy (ARH) in a gynecologic oncology fellowship training program. We prospectively collected cases of all of the patients with cervical cancer treated with TLRH and pelvic lymphadenectomy by our division from 2000 to 2006. All of the patients from the TLRH group were matched 1:1 with the patients who had ARH during the same period based on stage, age, histological subtype, and nodal sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 27 publications
4
51
2
Order By: Relevance
“…The movement of optical tube and the switch of operation vision field can expose the hidden areas in laparotomy, making the procedures such as removal of paravaginal tissues and deep obturator lymph nodes more accurate and complete. The pelvic lymph node count in this study was 26.0±5.8, which was consistent with that reported by other scholars in recent years [10] .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The movement of optical tube and the switch of operation vision field can expose the hidden areas in laparotomy, making the procedures such as removal of paravaginal tissues and deep obturator lymph nodes more accurate and complete. The pelvic lymph node count in this study was 26.0±5.8, which was consistent with that reported by other scholars in recent years [10] .…”
Section: Discussionsupporting
confidence: 92%
“…After the operation the lymph nodes were found to have metastasis. The operative time, only 200.6±38.6 min, was about 100 min shorter than that reported at present by many scholars, and the average intraoperative blood loss (300 mL) was not significantly increased compared to other researches [10,15] . Our findings indicated that use of the surgical devices such as harmonic scalpel and bipolar electrocautery can reduce surgical time and improve the quality of surgery, and also facilitate the recovery.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…The recurrence rate of endometriosis after radical surgical treatment reported is approximately 3% [27][28]. All patients in this study, some with long-term follow-up (average follow-up 32 months with a range of 1-65 months), experienced significant pain relief after hysterectomy.…”
Section: Discussionmentioning
confidence: 80%
“…Other studies have concluded that the laparoscopic, or laparoscopic-assisted vaginal radical hysterectomy results in less overall morbidity, less blood loss, fewer transfusions, a shorter hospitalization (by 3 days), a longer surgical time, and equal recurrence rates as compared to the classical open management [32,33,34,35,36]. The only prospective randomized study published so far dealing with such a comparison looked at small FIGO IB tumors, with only 15 patients who were randomized to either laparoscopic-assisted vaginal radical hysterectomy or radical abdominal hysterectomy.…”
Section: Laparoscopic Versus Open Surgical Accessmentioning
confidence: 99%